The Relationship Between the Big Five Personality Traits and Job Satisfaction – A Pilot Study on a Sample of Croatian Seafarers - Slišković, Ana; Russo, Andrea; Mulić, Rosanda (Transactions on Maritime Science, 2022)
Over the past decade, research on seafarers' health, well-being, stress, and job satisfaction has increased. Previous studies on other work populations have shown the relationship between the Big Five personality traits and job satisfaction, but the significance of each trait of the Big Five model, as well as the size of the correlations, vary according to the characteristics of the samples, such as gender, age, and occupation. With a view of the lack of addressing this research topic in seafarers, this study aimed to examine the relationships between the five basic personality dimensions and seafarers' job satisfaction. The convenient sample consisted of 286 Croatian male seafarers aged between 18 and 65. Participants completed a questionnaire that included questions on sociodemographic characteristics, IPIP-50 inventory measuring five personality traits, Job Satisfaction Scale, and Seafarers' Job Satisfaction Scale. The results showed that both measures of job satisfaction correlated positively with emotional stability, conscientiousness, and extraversion. However, the general measure of job satisfaction additionally correlated positively with intellect/imagination, while the measure of maritime job satisfaction additionally correlated positively with agreeableness. Among the five personality traits, emotional stability proved to be the highest correlate for both measures of job satisfaction. This pilot study reveals significant correlations between the Big Five personality traits and seafarers' job satisfaction. The paper brings theoretical and practical discussions on the relationships between the Big Five personality traits and seafarers' general and specific job satisfaction. The study represents a call for further researchers to verify the obtained results on more representative samples of the seafarer population and to test the predictive validity of personality traits in explaining job satisfaction through longitudinal studies.